Taiwanese Nuns and Education Issues in Contemporary Taiwan - Li, Yu-Chen (Religions, 2022)
In this article, I discuss the Buddhist educational profile of nuns in contemporary Taiwan by introducing the development of monastic education for women. Taiwanese women’s mass ordination created a Buddhist renaissance after postwar Taiwan, a national ordination system based on monastic discipline, as well as the revival of monastic education. Both ordination and monastic education are very strong institutional settings for women’s monastic identity. Its findings, firstly, shed light on how the increased opportunities for women’s education in Taiwanese Buddhism have continuously attracted young female university students. Secondly, these so-called scholarly nuns come to Buddhist academies as students and eventually become instructors. These scholarly nuns elevate the standards of their Buddhist academies and use their original academic specializations to expand the educational curriculum of their school. The role of scholarly nuns in contemporary Taiwan exemplifies that Buddhism provides educational resources for women, as educational resources enhance women’s engagement in Buddhism.